The Development of a Prototype Curriculum Based on Traditional Games of Skipping Rope - Heri Yusuf Muslihin; Resa Respati; Nurwahidah Nurwahidah (Universitas Pendidikan Indonesia, 2024)
Curriculum is a tool for achieving educational goals. Changes to a curriculum cannot be avoided. The prototype is a new curriculum issued by the government for the improvement of learning due to the COVID-19 pandemic. A lack of understanding of the benefits of traditional games makes the researchers explore how to develop a prototype curriculum based on local wisdom and physical motor skills through the use of traditional skipping rope games in early childhood. Thus, this reason becomes an essential aim of this research. This study uses a qualitative approach, and the research method used is Design-Based Research (DBR). Research instruments are researchers and participants. The steps involved in data analysis in this study are data reduction (organizing data), data display (making detailed descriptions), and conclusion drawing/verification (interpretation and conclusion). The expected result of this study is that it can assist the curriculum development process through the traditional game activity of skipping rope.